Indigenizing Human Rights: First Nations, Self-Determination, and Cultural Identity - Peetush, Ashwani Kumar (2009)
In this paper I argue that with regard to Indigeneity, there is a profound irony at work in the purportedly emancipatory power of human rights discourse. On the one hand, it is clear that this discourse has made, and continues to make, a significant contribution in supporting Indigenous peoples to articulate their claims for cultural recognition and struggle for freedom and self-rule. On the other hand, I contend that this discourse has a detrimental effect: a Trojan horse of sorts. The discourse of rights brings along with it powerful theoretical commitments, assumptions, and institutions that are at odds with and that undermine what most Native communities in Canada take to be an essential component of their cultural identities and self-understandings. I contend that at the heart of this issue are profound philosophical tensions about notions such as the self, community, and agency. That is, the core tensions rest on ideas that most Canadians take to be basic or unquestionable. I show that such assumptions are not only not basic or unquestionable, but, in fact, grounded in Western liberal ideals. I argue that dialogue in this context requires understanding that human rights, or any form of a global ethic, needs to be recast within Indigenous self-understandings and beliefs if such a dialogue is to be authentically intercultural and fruitful.